A Study to Assess the Effectiveness of Planned Teaching on Knowledge Regarding Prevention of Nutritional Anemia among Adolescencents in Kasturba Vidya Mandir, Sevagram,Wardha (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: -Growth of all living organism depends on nutrition .In human being growth period is said tobe from conception to adolescence and after that nutrition is required for maintenance of body. Lot of workhas been done regarding role of nutrition during pregnancy, infancy and childhood but hardly any attentionis paid to the group called adolescence i.e. period between childhood and adulthood. The most prevalentnutritional condition is anaemia worldwide. Prevalence in India of anemia among young girls were 56 % andthis amount to an average 64 million girls at any point in time.Aim: To determine the effectiveness of planned teaching on knowledge regarding prevention of nutritionalanemia among adolescence.Materials and Methods: A pre-experimental pre-test, post-test research design was used to conduct thisstudy. The setting was selected in the Kasturba Vidya Mandir Sewagram,Wardha (Maharashtra) after getting ethical permission. Purposive sampling was the sampling method used tocollect data from 9th standard students on the basis of structured knowledge questionnaire. After collectingpre-test data, planned teaching was given for intervention regarding prevention of nutritional anemia toadolescencents. Seven days were provided to the samples for utilizing planned teaching which was organizedfor 45-50 minutes. Post-test information was gathered after seven days from the day of intervention. Thedata were described by frequency, percentage and t-test was used to describe the difference between pre-testand post-test knowledge score. Chi-square test was also used to find out the association between knowledgeof 9th standard students regarding prevention of nutritional anaemia and selected demographic variables.Results: There was a significant difference between pre-test and post-test knowledge scores interpreted thatplanned teaching on knowledge regarding prevention of nutritional anaemia among adolescencents wereeffective. Mean value of pretest was 10.10 and posttest was 19.08and standard deviation values of pretestwas ±2.27and posttest was ±2.21. The calculated t-value was 19.66and p-value was 0.000.Conclusion: - The study was effective because the post-test knowledge score improved than the pre-testknowledge score. So the planned teaching has proved to improve 9th standard students knowledge regardingprevention of nutritional anaemia.